Parametric study of UWB chipless RFID tag: an impulse interrogation approach - Hossain, A. K. M. Z.; Ibrahimy, Muhammad Ibn; Motakabber, S. M. A. (Asian Research Publishing Network (ARPN), 2015)
The ultra-wide band passive RFID system is receiving a great consideration for the researchers with the aim of substituting the conventional barcode system. The dimension of the chipless tag still rests as a big question that makes the use of tagging the object difficult as well as costly. Different backscattered signal with time delay can successfully be read which is generated from the conventional UWB chipless tag by impulse interrogation signal instead of continues chirp signal. This approach can reduce the dimension of the tag, but it is still challenging to obtain a useful size by reducing further and to make comparable to cost of a barcode. In this paper, approaches have been made to find out the proper dimension of the tag with the help of CST MWS. The relation between the patch length and the substrate length has been established and hence the tag dimension is determined as 81.4mm × 81.4mm.